A Good Death. Issue 2 (29th July 2016) - DORSEY, DALE
Abstract : Largely in response to Epicurus' famous challenge, philosophers have been quite imaginative in coming up with ways in which death is bad. Most often, death is described as an instrumental bad. Given that I would have obtained additional welfare benefits had I not died when I did, my death causes me to miss out on intrinsic goods I might otherwise have obtained. In this article, however, I argue that the standard account (and its corollaries) misses an important feature of the dis/value of death. I argue that some deaths can be good – intrinsically good – for the person who dies.